Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


Use quadratic equation
and beta==[-b-sqrt(b^2-4ac)]/2a
where a=1 b=1 c=1

then get the ans as
x2 + x - 1=(x-alpha)(x-beta)

2 2 2
thanks last question
of the day .....
this was
haha okay
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts